Elk resource selection at parturition sites, Black Hills, South Dakota. Issue 3 (15th November 2015) - Lehman, Chadwick P.; Rumble, Mark A.; Rota, Christopher T.; Bird, Benjamin J.; Fogarty, Dillon T.; Millspaugh, Joshua J.
ABSTRACT: We studied elk ( Cervus canadensis nelsoni ) parturition sites at coarse (314‐km 2 and 7‐km 2 ) and fine (0.2‐ha) scales in the Black Hills, South Dakota, 2011–2013, following a period of population decline and poor calf recruitment. Our objective was to test whether female elk selected parturition sites across spatial scales in association with forage, terrain ruggedness, road density, or hiding and security cover. At coarse scales in forests and grasslands, female elk selected sites in areas with greater proportions of vegetation communities that provided forage (56–74% of area) and more rugged topography (194–248 m) than found at random. At coarse scales in grasslands, elk selected sites in areas with lower road densities (≤1.24 km/plot). At the fine scale in forests and grasslands, female elk selected sites in areas with intermediate slope (19%), closer to water (355–610 m), and far from roads (541–791 m). Further, elk in forests and grasslands selected sites with intermediate security cover (50–88 m). We hypothesize elk selected for intermediate rugged terrain at larger scales for security from high road densities and human disturbance, but these areas may have placed elk in riskier environments for puma ( Puma concolor ) predation. Forest management that maintains open‐canopied vegetation communities in less rugged areas and prevents ponderosa pine ( Pinus ponderosa ) encroachment of meadows to provide forage may be beneficial for elk. Further, elk parturition sites occurred close to roads, particularly on public lands, and agencies should consider road‐use restrictions and vegetation buffers beside roads in areas with less rugged terrain, which may provide favorable calving habitat. © 2015 The Wildlife Society.